Uncommon presentation of CAPD-related peritonitis with unusual organism: Kocuria kristinae. Case report and review of the literature - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; TUĞLULAR, ZÜBEYDE SERHAN (MARMARA UNIV, FAC MEDICINE, 2017)
Kocuria kristinae is a gram-positive coccus of Micrococcaceae family. Kocuria kristinae inhabits the skin and mucous membranes. It can cause opportunistic infections in patients with indwelling devices and severe underlying diseases. We describe here a case of acute peritonitis caused by Kocuria kristinae in a patient on continuous ambulatory peritoneal dialysis (CAPD). Additionally, a review of other reported CAPD related peritonitis by Kocuria kristinae is provided. The importance of Kocuria kristinae as a pathogen in patients with CAPD peritonitis should not be underestimated.
Keywords: Back pain; Kocuria kristinae; Peritonitis; Peritoneal dialysis; BACTEREMIA